Plant seed-inspired cell protection, dormancy, and growth for large-scale biofabrication - Pan, Matthew Houwen (2021)
Biofabrication technologies have endowed us with the capability to fabricate complex biological constructs. However, cytotoxic biofabrication conditions have been a major challenge for their clinical application, leading to a trade-off between cell viability and scalability of biofabricated constructs. Taking inspiration from nature, we proposed a cell protection strategy which mimicks the protected and dormant state of plant seeds in adverse external conditions and their germination in response to appropriate environmental cues. Applying this bioinspired strategy to biofabrication, we successfully preserved cell viability and enhanced the seeding of cell-laden biofabricated constructs via a cytoprotective pyrogallol (PG)-alginate encapsulation system. Our cytoprotective encapsulation technology utilizes PG-triggered sporulation and germination processes to preserve cells, is mechanically robust, chemically resistant, and highly customizable to adequately match cell protectability with cytotoxicity of biofabrication conditions. More importantly, the facile and tunable decapsulation of our PG-alginate system allows for effective germination of dormant cells, under typical culture conditions. With this approach, we have successfully achieved a biofabrication process which is reproducible, scalable, and provided a practical solution for off-the-shelf availability, shipping and temporary storage of fabricated bio-constructs.